THE INFLUENCE OF CONSUMER ATTITUDES AND CONSUMER MOTIVATION ON PURCHASING DECISIONS THROUGH SHOPEE (Study on D-IV Marketing Management Students at State Polytechnic of Malang) - Aisyahrani Anam; Musthofa Hadi (Transpublika Publisher, 2024)
In the current technological era, online shopping has become a dominant trend. With easy internet access and rapid technological advancements, society increasingly relies on e-commerce platforms like Shopee for their shopping needs. This study aims to analyze the influence of consumer attitudes and motivation on purchasing decisions on Shopee. This quantitative research involved distributing questionnaires to 77 D-IV Marketing Management students from the Business Administration Major for the 2023/2024 academic year who have made purchases on Shopee. Accidental sampling was used, and data were analyzed using multiple linear regression (Y = a + b1X1 + b2X2 + e) and hypothesis testing. The findings show that consumer attitude does not have a partial effect on purchase decisions, while consumer motivation does. Collectively, both variables significantly influence purchase decisions, contributing 85.7% to the purchase decision, with 14.3% influenced by other factors. The study concludes that only consumer motivation significantly impacts purchasing decisions. Shopee should more strictly filter sellers by verifying addresses, product types, and availability to avoid pre-orders. Additionally, Shopee can improve information quality on prices, availability, and product benefits, and enhance transaction security to improve user safety and application ratings, thereby building positive consumer perception.